2005
DOI: 10.1007/s00432-005-0026-z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of novel N-sulfonylpyrimidine derivatives on the growth of anaplastic mammary carcinoma in vivo

Abstract: In this work it has been found that N-1-sulfonylcytosine derivatives have strong antitumor activity against mouse mammary carcinoma which is a good reason for further research of these compounds both in experimental and preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…N1-sulfonylcytosine derivatives 3-6 were prepared by the condensation of pyrimidine bases with different sulfonyl chlorides, and then transformed to C5-substituted N1-sulfonylcytosines (8,(12)(13)(14)(15) in moderate to very good yield (up to 65%). Microwave assisted reaction significantly shortened the reaction time and favored formation of Mannich product over numerous possible byproducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N1-sulfonylcytosine derivatives 3-6 were prepared by the condensation of pyrimidine bases with different sulfonyl chlorides, and then transformed to C5-substituted N1-sulfonylcytosines (8,(12)(13)(14)(15) in moderate to very good yield (up to 65%). Microwave assisted reaction significantly shortened the reaction time and favored formation of Mannich product over numerous possible byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonylated derivatives of cytosine, that we have described earlier, have shown strong antiproliferative activity against human tumor cell lines in vitro [7][8][9][10][11][12] and in vivo 13 . These findings encouraged us to further investigate modified pyrimidines.…”
Section: Introductionmentioning
confidence: 99%
“…TsC and its two derivatives, namely 1-(p-toluenesulfonyl)cytosine hydrochloride (TsC×HCl) and zinc(II) complex [Zn(II)(TsC) 2 ] were shown to have a strong antitumour activity against mouse mammary carcinoma in vivo [26]. Toxicological studies in vivo showed that TsC and TsC × HCl have no significant influence on the peripheral blood thrombocyte number, red blood cell count or haemoglobin levels, while significant deviations from the untreated control group were detected in the peripheral white blood cell count [27].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] We have recently shown that N-sulfonylpyrimidine derivatives of type I (Figure 1) possess strong antitumor activity under in vitro and in vivo conditions. [8][9][10][11] In comparison with 5-FU (5-fluorouracil), some of the N-sulfonylpyrimidine derivatives showed up to 10 times stronger growth inhibitory effects on a number of tested tumor cells while the effects on normal human fibroblasts were much less pronounced. 12 These types of nucleic base sulfonamides were found to inhibit DNA, RNA and protein synthesis and induce apoptosis in human tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In vivo experiments showed that some N-sulfonylcytosine derivatives exhibited strong antitumor activity against mouse mammary carcinoma. 9,14 To further explore the biological potential of this type of molecules, their structure was modified by combining them with another potent anticancer pharmacophore -that of amidine. The amidine group is present in many compounds capable of interacting with a wide range of biological targets, resulting in anti-degenerative, anticancer and antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%